Tourism and Foreign Direct Investment Inflows in Sri Lanka. Issue 2 (September 2019) - Ravinthirakumaran, K.; Selvanathan, E. A.; Selvanathan, S.; Singh, T.
This article examines the relationship between tourism and foreign direct investment (FDI) and the factors that enhance tourism in Sri Lanka using data over the years 1978–2015, under a vector autoregressive framework. The results reveal that there is a significant long-run equilibrium relationship between tourism, and a number of variables such as FDI, exchange rate, tourism price and civil war of the country. The results also reveal that there exist unidirectional causal relationships from FDI to tourism and tourism price to tourism, in both the long run and the short run. In light of this finding, it is recommended that Sri Lanka should introduce policies that would increase FDI inflows into the tourism industry and maintain a competitive tourism price to attract more tourist arrivals. JEL: C32, F19, F41, O53